Controlled synthesis and morphology dependent luminescence of Lu2O2S:Eu3+ phosphors. Issue 10 (19th January 2016) - Zhang, Bowen; Zou, Haifeng; Dai, Yunzhi; Song, Yanhua; Zheng, Keyan; Zhou, Xiuqing; Sheng, Ye
Abstract : The dependence of Lu2 O2 S:Eu 3+ luminescence performance on different morphologies has been explored and possible reasons are proposed. Abstract : Lu2 O2 S:Eu 3+ phosphors were successfully prepared with controllable morphology, including 3D sphere-like, cloud-like, nested tetrahedron, flower-like and 1D rod-like architectures. It is indicated that the pH value of the system plays an important role in the morphology and the degree of crystallinity of the product. Interestingly, with morphological changes, the band gap energy of the Lu2 O2 S crystal changed, followed by a variation of the crystal field symmetry and furthermore the luminescence performance. Therefore, such a morphology-sensitive luminescence property was first interpreted in terms of degree of crystallinity, band gap energy, and the crystal field symmetry around Eu 3+ .